LABORATORY AND CASE STUDIES OF THERMAL CYCLING AND STORED STRAIN ON THE STABILITY OF SELECTED MARBLES - Logan J.M. (My University, 2004)
Studies of marble panels from the exterior of two buildings document the processes leading to bowing of the material. Bowing of panels is most extensive in those areas that are exposed to direct or reflected thermal energy. The thermal anisotropic behavior of calcite results in grain-boundary separation, grain sliding and microfracturing. The resulting loss of strength is one factor leading to bowing. The development of bows further reduces the panel strength as the outer portions elongate by inelastic deformation mechanisms. Laboratory experiments cycling marble samples for over 200 cycles at three temperatures up to 107C above room conditions show similar strength losses as the natural situation. The second factor contributing to the bowing process is the release of residual elastic strain. The strain is in part stored in the marble from its geologic history, but may also be accumulated during thermal cycling due to the properties of calcite. Marble panels have been found to bow when stored outside, but not attached to any framework, indicating that the release of residual strain is a critical factor in producing the bows.